Experimental study on the effect of spray evaporative condensation on air conditioning performance - HUANG Xiang; HU Jian; SU Lin; CHU Junjie; YAN Libo; YANG Liu; WANG Xin (Xi'an Gongcheng Daxue xuebao)
In order to reduce the energy consumption of air conditioning units in high-temperature working conditions and improve the energy efficiency ratio of the units, this study proposes to apply the spray evaporative condensation technology to air conditioning condensers. Firstly, the water flow required for spraying was theoretically calculated, and the nozzles were used to cool the V-type condenser of air conditioner; then, in the standard enthalpy difference laboratory, the relevant experimernts of different distances between the nozzles and the condenser, different injection angles and intermittent spray were carried out, and the energy-saving effect of spray under different working conditions were analyzed. The results show that the spray evaporation condensation technology applied to the condenser has a better energy-saving effect. The optimal installation distance between the nozzle and condenser is 40 cm, the optimal spray angle of the nozzle is 60°, in the indoor dry bulb temperature of 37 ℃, outdoor dry/wet bulb temperature of 35/27 ℃, the energy efficiency ratio of the unit increases from 4.0 to 4.89, the energy efficiency improvement rate is 22.2%, and the energy efficiency improvement rate decreases with the drop of the outdoor temperature. The technology is more suitable for high-temperature areas. It can provide a reference for the application of the technology in air conditioner condenser.